2007
DOI: 10.1086/522965
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Development ofPlasmodiumLiver Stage–Specific Memory CD8+T Cells during the Course of Blood‐Stage Malarial Infection

Abstract: Immunity to Plasmodium liver stages in individuals in malaria-endemic areas is inextricably linked to concomitant blood-stage parasitemia. Although Plasmodium sporozoite infection induces measurable CD8+ T cell responses, the development of memory T cells during active erythrocytic infection remains uncharacterized. Using transgenic T cells, we assessed antigen-specific effector CD8+ T cell responses induced by normal (NorSpz) and radiation-attenuated (IrrSpz) Plasmodium yoelii sporozoites. The magnitude, phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…It has been reported that blood-stage infection can impair immunity to liver-stage antigens [24], though this is disputed by evidence that there is an equivalent response by liver-stage-specific transgenic T cells to sporozoites in the presence or absence of a subsequent blood-stage infection [32]. To resolve this issue with respect to CD8 + T cell-mediated immunity, we examined the expansion of PbT-I cells after exposing mice to live sporozoites (which will infect the liver then generate blood-stage infection), or irradiated sporozoites alone or followed by blood-stage (iRBC) infection 2 days later, mimicking the time for blood-stage egress after live sporozoite infection ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that blood-stage infection can impair immunity to liver-stage antigens [24], though this is disputed by evidence that there is an equivalent response by liver-stage-specific transgenic T cells to sporozoites in the presence or absence of a subsequent blood-stage infection [32]. To resolve this issue with respect to CD8 + T cell-mediated immunity, we examined the expansion of PbT-I cells after exposing mice to live sporozoites (which will infect the liver then generate blood-stage infection), or irradiated sporozoites alone or followed by blood-stage (iRBC) infection 2 days later, mimicking the time for blood-stage egress after live sporozoite infection ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study extends this concept by indicating that CD8 + T cells of a single specificity for a blood-stage antigen can protect against liver-stage infection when the antigen is also expressed during the liver stage. It has been reported that blood-stage infection can impair immunity to liver-stage antigens [24], though this is disputed by the above study, which uses blood-stage infection to induce anti-sporozoite immunity [25] and by another study that shows an equivalent response by liver-stage-specific transgenic T cells to sporozoites in the presence or absence of a subsequent blood-stage infection [32]. The availability of PbT-I cells will give us the opportunity to examine this relationship when the relevant antigen is expressed during both blood- and liver-stages and to determine how antigens presented during the blood-stage might influence the effector function of T cells capable of recognizing liver-stage antigens.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, suppressive treatment with chloroquine was intended to exclude potential suppression of immune responses against preerythrocytic-stage parasites by an existing infection with asexual blood-stage parasites. More recently, robust induction of effector and memory CD8 ϩ T cell responses was shown to occur even in the presence of parasites in the erythrocytic cycle [7].Clinical studies of 8-aminoquinolines such as primaquine [8] and tafenoquine [9] for malaria chemoprophylaxis revealed an unusually prolonged delay to the onset of reinfection; in the case of tafenoquine, the delay was Ͼ6 times the plasma half-life. These observations, together with early indications of a protective effect of primaquine treatment [5], led us to hypothesize that repeated pharmacological ablation of liver-stage Plasmodium parasites has the potential to induce strong protective immune responses against sporozoite-induced malaria.…”
mentioning
confidence: 99%
“…Notably, suppressive treatment with chloroquine was intended to exclude potential suppression of immune responses against preerythrocytic-stage parasites by an existing infection with asexual blood-stage parasites. More recently, robust induction of effector and memory CD8 ϩ T cell responses was shown to occur even in the presence of parasites in the erythrocytic cycle [7].…”
mentioning
confidence: 99%
“…One study reported that the blood stage parasites inhibit Dendritic Cells (DC) function by altering its antigen presentation capacity thus precluding the induction of efficient liver stage immunity (Ocana-Morgner et al, 2003). Using the P. yoelli CSP-TCR transgenic model, an independent study confirmed identical patterns of activation and differentiation of CD8+ T cells following exposure to either normal or radiation attenuated sporozoites (Hafalla et al, 2007). Importantly, the effector and recall responses of memory CD8+ T cells were unaltered in the presence or absence of an ongoing blood stage infection.…”
Section: Effect Of Concomitant and Super Infections On Eef Developmentmentioning
confidence: 91%